Comparing the effects of tranquilisation with long-acting neuroleptics on blue wildebeest (Connochaetes taurinus) behaviour and physiology - Laubscher, Liesel L. (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.